1980
DOI: 10.1021/ja00546a026
|View full text |Cite
|
Sign up to set email alerts
|

Naphthonitrile-alkene exciplexes. Use of tethered chromophores to probe geometric factors in exciplex formation and decay

Abstract: Sir:The aryl nitrile-olefm systems are interesting because they show exciplex fluorescence' as well as photoreactions. These allow Hamilton, Ontario, Canada U S 4Ml

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…[9] The related intramolecular photocycloaddition of 6 c was reported by McCullough et al to give two types of [2+2] photocycloadducts, 7 c and 8 c, with 7 c as the major product (Scheme 3). [4] We had previously studied the related reactions of 6 a-e and obtained products to which we originally assigned structures 7 a-e and 8 a-e, by analogy with the assignment of McCullough et al [5] We have found recently that the product ratios of both product types in the photoreactions of 6 a-e are dependent on additives and solvents. In addition, the major products 7 a-e gradually reverted to the starting compounds 6 a-e, but the minor products were stable under the reaction conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] The related intramolecular photocycloaddition of 6 c was reported by McCullough et al to give two types of [2+2] photocycloadducts, 7 c and 8 c, with 7 c as the major product (Scheme 3). [4] We had previously studied the related reactions of 6 a-e and obtained products to which we originally assigned structures 7 a-e and 8 a-e, by analogy with the assignment of McCullough et al [5] We have found recently that the product ratios of both product types in the photoreactions of 6 a-e are dependent on additives and solvents. In addition, the major products 7 a-e gradually reverted to the starting compounds 6 a-e, but the minor products were stable under the reaction conditions.…”
mentioning
confidence: 99%
“…
Photocycloaddition of unsaturated compounds to aromatic rings is a useful and convenient method for the construction of polycyclic compounds in organic synthesis. [1][2][3][4][5][6][7] In particular, the inter-and intramolecular metaphotocycloaddition of alkenes to benzene rings has been extensively developed from the synthetic and mechanistic points of view in recent decades. [1,2] Wender et al first reported the synthesis of natural products by using an intramolecular meta-photocycloaddition as a key step.
…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In particular, the inter-and intramolecular metaphotocycloaddition of alkenes to benzene rings has been extensively developed from the synthetic and mechanistic points of view in recent decades. [1][2][3][4][5][6][7] In particular, the inter-and intramolecular metaphotocycloaddition of alkenes to benzene rings has been extensively developed from the synthetic and mechanistic points of view in recent decades.…”
mentioning
confidence: 99%
“…However, prolonged irradiation afforded 3 b as the sole product in a highly Scheme 1. [4] We had previously studied the related reactions of 6 a-e and obtained products to which we originally assigned structures 7 a-e and 8 a-e, by analogy with the assignment of McCullough et al [5] We have found recently that the product ratios of both product types in the photoreactions of 6 a-e are dependent on additives and solvents. Irradiation of isolated 2 b quickly gave 1 b; clearly, the [2+2] cycloaddition in this system is reversible.…”
mentioning
confidence: 99%
See 1 more Smart Citation